Intergenerational toxicity of flonicamid in zebrafish: Immune-inflammatory stress as a driver of parental and offspring effects - Ruiqiang Fu; Hongli Liu; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu; Lan Zhang (Journal of Environmental Sciences, 2026)

An ultrasound-activated PLLA@BaTiO3&SF Janus membrane enhances fracture healing via synergistic piezoelectricity and bioactivity - Qinghua Guo; Jiahao Cao; Zixian Yang; Wei Cao; Hongli Chen; Yidi Duan; Xu Wang; Zhen Gong; Xiaolin Liu; Shanshan Fu; Yibin Huang; Yafei Feng; et al. (Chemical Engineering Journal, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Chiral Ratiometric Fluorescent Silicon Nanoparticles for “Turn-on” Enantioselective Recognition of Tryptophan - Chen Liu; Yaning Duan; Cancan Lu; Yu Fu; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2026)

Dual role of functional bacterial agent based on Bacillus subtilis coupled with smooth vetch (Vicia villosa var.) on cadmium-contaminated soil: Synergistic passivation and nutrient supply - Qiwen An; Jie Liu; Yitong Liu; Fuxuan Bi; Zonghao Dong; Xu Liu; Zhao Jiang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Enhanced catalytic degradation activity through quenching introduces Pd doping in TiO2 derived from NH2-MIL-125(Ti) - Jinqiang Fu; Fenglan Liang; Wenjing Zhong; Tao Kuang; Ziyuan Yin; Yongshi Li; Zhenggui Huang; Hongli Liu; Deyun Ma (Environmental Research, 2025)

Microalgal glutaredoxin 1 interacts with transcription factor bZIP to resist cadmium stress via lipid metabolism alteration - Chao Xing; Xuan Fu; Yaru Du; Kui Liu; Hongli Yuan; Jin Liu; Jinshui Yang (Bioresource Technology, 2025)

Mineralogical investigation of modern sediments and source analysis of different grain-size fractions in the middle and lower Yellow River - Dianbao Chen; Wei Liu; Hongli Pang; Xiangnan Fu; Donghong Hu; Ke Wang; Dexuan Chen; Duo Huang; Baotian Pan; Eduardo Garzanti (Geomorphology, 2025)

A recyclable magnetic polyethyleneimine-functionalized cellulose aerogel for reducing cadmium (Cd) accumulation in acidic contaminated soil: Stress mitigation and soil improvement mechanisms - Fuxuan Bi; Zhao Jiang; Zhiyu Zhang; Zhan Zhang; Mengning Wang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Influence of surface cover type on sediment transport capacity and sediment retardation benefits based on flume experiments - Kai Zhang; Ning Li; Suhua Fu; Hongli Mu (Soil and Tillage Research, 2025)

The mechanism of surface cover influences the sediment transport capacity - Kai Zhang; Ning Li; Suhua Fu; Hongli Mu; Bingjun Lu (Journal of Hydrology, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

Nanozyme bionics mitochondrial revitalizer suppresses ferroptosis in nucleus pulposus cells for disc regeneration - Jinghao Qin; Yanqiu Wang; Lu Tan; Yi Yang; Yeqin Fu; Conghui Wu; Hongli Duan; Changqing Li; Hongli Li; Shen Zhou; Yue Zhou; Minghan Liu (Chemical Engineering Journal, 2025)

Preparation of water-soluble dietary fiber from bamboo shoots by fungi fermentation and its supplementation in biscuits - Ying Shen; Ling Yang; Hong Peng; Limin Shen; Guiming Fu; Yin Wan; Yuhuan Liu; Xiaodan Wu; Hongli Zheng (Food and Bioproducts Processing, 2024)

N-desmethyldauricine from Menispermum dauricum DC suppresses triple-negative breast cancer growth in 2D and 3D models by downregulating the NF-κB signaling pathway - Wenting Liu; Yan Yu; Tao Hou; Hongli Wei; Fangbin Lv; Aijin Shen; Yanfang Liu; Jixia Wang; Dongmei Fu (Chemico-Biological Interactions, 2024)

Analysis of sea level variability and its contributions in the Bohai, Yellow Sea, and East China Sea - Yanxiao Li; Jianlong Feng; Xinming Yang; Shuwei Zhang; Guofang Chao; Liang Zhao; Hongli Fu (Frontiers in Marine Science, 2024)
Understanding the sea level variability of the Bohai, Yellow Sea, and East China Sea (BYECS) is crucial for the socio-cultural and natural ecosystems of the coastal regions. In this study, based on satellite altimetry data, selected time range from 1993 to 2020, using the cyclostationary empirical orthogonal function (CSEOF) analysis method distinguishes the primary sea level variability modes. The analysis encompasses the seasonal signal, trend, and El Niño-Southern Oscillation (ENSO) associated mode of sea level anomaly. The amplitude of the annual cycle demonstrates a non-stationary signal, fluctuating between -15% and 15% from the average. Monsoons, atmospheric forcing, ocean circulation, wind-driven Ekman transport, and the Kuroshio emerge as the primary factors influencing BYECS variability on seasonal scales. The satellite altimetry sea level exhibits an average trend within the range of 3-4 mm/year, while the steric sea level trend is generally smaller, falling within the range of 0-2 mm/year. Throughout the entire period, the contribution of steric sea level to the mean sea level trend consistently remains below 25%. Furthermore, BYECS sea level variations have a sensitive response to strong El Niño years, with a clear regionalization of the response, which is related to the intricate atmospheric circulation and local wind pressures, as well as the influence of ocean circulation. In conclusion, we gained a more comprehensive understanding of sea level variability in the BYECS, especially the annual cycle of sea level amplitude and the response of ENSO. However, more studies still need to be done to differentiate the various factors in sea level variations.

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Imidacloprid affects the visual behavior of adult zebrafish (Danio rerio) by mediating the expression of opsin and phototransduction genes and altering the metabolism of neurotransmitters - Ruiqiang Fu; Hongli Liu; Yanning Zhang; Liangang Mao; Lizhen Zhu; Hongyun Jiang; Lan Zhang; Xingang Liu (Science of The Total Environment, 2024)

Response of sound propagation characteristics to Luzon cold eddy coupled with tide in the Northern South China Sea - Yu Liu; Xuefeng Zhang; Hongli Fu; Zhiwen Qian (Frontiers in Marine Science, 2023)
The northern part of the South China Sea is a complex ocean environment with a large range of tidal waves and the stable Luzon cold eddy, which significantly influence the sound propagation characteristics through their impact on sound speed. This study uses a 3D ocean-acoustic framework consisting of MITgcm and BELLHOP ray model to investigate the coupled effects of the Luzon cold eddy and tidal waves. Firstly, the model incorporates tidal assimilation to reconstruct the hydrographic field and compute the sound speed field. Subsequently, the sound propagation in a representative region in the northern South China Sea is simulated to compare the response of sound propagation characteristics to the Luzon cold eddy only, tide only, and the coupled effect of both. The results demonstrate that the cold eddy shifts the location of the convergence zone forward by over 5 km at most. Further, it also makes the acoustic energy focus on the first few arrivals and delays the arrival time of rays by about 0.1 s. The tidal waves intensify these effects, resulting in a further increase of the forward distance of the convergence zone by 2-5 km and a delay in arrival time by 0.02 s. Sound propagation in the coupled influence of these two dynamic processes is exposed to steady perturbations from the cold eddy and spatial-temporal perturbations from tidal waves. The model in this study provides valuable insight for underwater detection and positioning in the realistic ocean environment.

Engineering the S-scheme heterojunction between NiO microrods and MgAl-LDH nanoplates for efficient and selective photoreduction of CO2 to CH4 - Hongli Yang; Huilin Hou; Man Yang; Zhongli Zhu; Hui Fu; Dongdong Zhang; Yong Luo; Weiyou Yang (Chemical Engineering Journal, 2023)

Natural phosphorus-ferromanganese ore-based composites for the simultaneous remediation of arsenic- and lead-co-contaminated groundwater: synergistic effectiveness, kinetics, and mechanisms - Hongli Lu; Xiangjian Xu; Yu Yang; Han Xiao; Fu Xia; Xu Han; Sheng Deng; Shuxuan Wu; Xingang Wang; Yonghai Jiang; Qinghua Yan (Environmental Science and Pollution Research, 2023)

Transcriptional regulation of tomato fruit quality - Hongli Li; Gangshuai Liu; Daqi Fu (Postharvest Biology and Technology, 2023)

Anisotropic diffusion filters for flow-dependent variational data assimilation of sea surface temperature - Yan Hu; Xuefeng Zhang; Dong Li; Wei Li; Lianxin Zhang; Hongli Fu; Liang Zhang (Ocean Modelling, 2023)

Heterogeneous reaction of NO2 with feldspar, three clay minerals and Arizona Test Dust - Mingjin Tang; Xiaohong Jia; Lanxiadi Chen; Wenjun Gu; Chengpeng Huang; Fu Wang; Lan Luo; Hongli Wang; Xinming Wang; Chao Peng (Journal of Environmental Sciences, 2023)

NAC transcription factor NOR-like1 regulates tomato fruit size - Zhenzhen Peng; Hongli Li; Gangshuai Liu; Wen Jia; Daqi Fu (Planta, 2023)

Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Hongli Fu; Bo Dan; Zhigang Gao; Xinrong Wu; Guofang Chao; Lianxin Zhang; Yinquan Zhang; Kexiu Liu; Xiaoshuang Zhang; Wei Li (Frontiers in Marine Science, 2023)
We present the China Ocean ReAnalysis version 2 (CORA2) in this paper. We compare CORA2 with its predecessor, CORA1, and with other ocean reanalysis products created between 2004 and 2019 [GLORYS12v1 (Global Ocean reanalysis and Simulation), HYCOM (HYbrid Coordinate Ocean Model), GREP (Global ocean Reanalysis Ensemble Product), SODA3 (Simple Ocean Data Assimilation, version 3), and ECCO4 (Estimating the Circulation and Climate of the Ocean, version 4)], to demonstrate its improvements and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved owing to an enhanced resolution of 9 km and updated data assimilation scheme compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products studied. The subsurface temperature (salinity) RMSE of CORA2, at 0.87°C (0.15 psu), is comparable to that of SODA3, smaller than that of ECCO4, and larger than those of GLORYS12v1, HYCOM, and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variations in subsurface temperature and salinity than the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region, as those of GREP and GLORYS12v1 do, it is more effective than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations in steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of the steric sea level of CORA2 is closer to that of GREP than that of the other products, and the long-term warming trends of global OHC in the high-resolution CORA2 and GLORYS12v1 are greater than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it still achieves good results from 2009 onward. We plan to further improve CORA2 by assimilating the best available observation data using the incremental analysis update (IAU) procedure and improving the SLA assimilation method.

Integrate transcriptomic and metabolomic analysis reveals the underlying mechanisms of behavioral disorders in zebrafish (Danio rerio) induced by imidacloprid - Hongli Liu; Ruiqiang Fu; Yanning Zhang; Liangang Mao; Lizhen Zhu; Lan Zhang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

Geographic-dependent variational parameter estimation: A case study with a 2D ocean temperature model - Zhenyang Du; Xuefeng Zhang; Dong Li; Zhiyuan Zhang; Lianxin Zhang; Hongli Fu; Liang Zhang (Journal of Marine Systems, 2023)

A multi-scale high-order recursive filter approach for the sea ice concentration analysis - Lu Yang; Dong Li; Xuefeng Zhang; Hongli Fu; Kexiu Liu (Acta Oceanologica Sinica, 2022)

The impact of biogenic emissions on ozone formation in the Yangtze River Delta region based on MEGANv3.1 - Yangjun Wang; Xingjian Tan; Ling Huang; Qian Wang; Hongli Li; Hongyan Zhang; Kun Zhang; Ziyi Liu; Dramane Traore; Elly Yaluk; Joshua S. Fu; Li Li (Air Quality, Atmosphere & Health, 2021)

A variational successive corrections approach for the sea ice concentration analysis - Xuefeng Zhang; Lu Yang; Hongli Fu; Dong Li; Zheqi Shen; Lianxin Zhang; Xuhui Hu (Acta Oceanologica Sinica, 2020)

Influence of soil and water conservation measures on soil fertility in the Beijing mountain area - Hongli Mu; Suhua Fu; Baoyuan Liu; Bofu Yu; Aijuan Wang (Environmental Monitoring and Assessment, 2018)

High-yield production of canine parvovirus virus-like particles in a baculovirus expression system - Hongli Jin; Xiaohong Xia; Bing Liu; Yu Fu; Xianping Chen; Huihui Wang; Zhenqiang Xia (Archives of Virology, 2016)

Assessment of intraseasonal variabilities in China Ocean Reanalysis (CORA) - Min Zhang; Lei Zhou; Hongli Fu; Lianghong Jiang; Xiangming Zhang (Acta Oceanologica Sinica, 2016)

A study of transport and impact strength of Fukushima nuclear pollutants in the north pacific surface - Hongli Fu; Wei Li; Xuefeng Zhang; Guijun Han; Xidong Wang; Xinrong Wu; Lianxin Zhang (Journal of Ocean University of China, 2014)

A global ocean reanalysis product in the China Ocean Reanalysis (CORA) project - Guijun Han; Hongli Fu; Xuefeng Zhang; Wei Li; Xinrong Wu; Xidong Wang; Lianxin Zhang (Advances in Atmospheric Sciences, 2013)

An ensemble estimation of impact times and strength of Fukushima nuclear pollution to the east coast of China and the west coast of America - GuiJun Han; Wei Li; HongLi Fu; XueFeng Zhang; XiDong Wang; XinRong Wu; LianXin Zhang (Science China Earth Sciences, 2013)

A new version of regional ocean reanalysis for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Xidong Wang; Xinrong Wu; Hongli Fu; Xiaoshuang Zhang; Lianxin Zhang; Dong Li (Advances in Atmospheric Sciences, 2013)

Improvement of short-term forecasting in the northwest Pacific through assimilating Argo data into initial fields - Hongli Fu; Peter C. Chu; Guijun Han; Zhongjie He; Wei Li; Xuefeng Zhang (Acta Oceanologica Sinica, 2013)

Toxicity and influences of the alkaloids from Cynanchum komarovii AL. Iljinski (Asclepiadaceae) on growth and cuticle components of Spodoptera litura Fabricius (Noctuidae) larvae - Hongli Sun; Simon Blanford; Yanyan Guo; Xuejiao Fu; Wangpeng Shi (Natural Product Research, 2012)

Investigation of polynya dynamics in the northern Bering Sea using greyscale morphology image-processing techniques - Hongli Fu; Jinping Zhao; Karen E. Frey (International Journal of Remote Sensing, 2012)

The Reanalysis of Currents and Throughflow Volume Transport in the Taiwan Strait - Ting Yu; Zengan Deng; Guijun Han; Xinrong Wu; Hongli Fu; Kejian Wu (Marine Geodesy, 2012)

Formation and transportation of high-salinity water produced in polynyas south of the St. Lawrence Island - Hongli Fu; Jinping Zhao; Jiuxin Shi; Yutian Jiao (Journal of Ocean University of China, 2010)

Protective effects of N-acetylcysteine in isoproterenol-induced myocardium injury in rats - Bin Liu; Weimin Li; Yue Li; Zhonghua Wang; Hongli Li; Ping Liu; Jun Fu (Molecular Biology Reports, 2009)